PENGARUH PELATIHAN PARTISIPATIF INTERAKTIF DAN MOTIVASI KEWIRAUSAHAAN TERHADAP MINAT BERUSAHA MASYARAKAT DI DESA TELUK LATAK BENGKALIS - Wan Junita Raflah; Adrian Irnanda Pratama (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2020)
This study aims to determine the effect of entrepreneurship training and entrepreneurial motivation on entrepreneurial interest in the village of Teluk Latak Bengkalis. This research is used for the process of monitoring and evaluation for the Bengkalis State Polytechnic community service team in the future to formulate a better program in increasing the interest of entrepreneurs in the target community groups. This type of research is explanatory research or explanatory research using hypothesis testing using quantitative approaches. The sample in this study was the community group of Teluk Latak Village, Bengkalis District, Bengkalis Regency, amounting to 35 people. The data analysis method used is multiple linear regression. The partial t-test results on the entrepreneurship training variable have Sig. (0.013 and t-test 2,645). Partial t-test results on entrepreneurial motivation variables have Sig. (0.016 and t-count 2,556). Multiple linear regression summary output models have a coefficient of determination of R Square of 39.9%. It can be concluded that entrepreneurship training and entrepreneurial motivation can increase interest in entrepreneurship